Analysis of the dynamics of the Russian Federation's Greco-Roman wrestling team's medal count at world championships - Fedorov, G.P.; Levitskiy, A.G.; Denisenko, A.N. (Theory and Practice of Physical Culture, 2026)
Abstract Objective of the study is to analyse the dynamics of the Russian national team's success at world championships in Greco-Roman wrestling. Methods and structure of the study. An analysis of the Russian national team's medal count in Greco-Roman wrestling at world championships between 1996 and 2024 was conducted. The study covers seven four-year training cycles. Results and conclusions. Based on an analysis of statistical data, the results of our wrestlers' performances are examined in terms of their dominance on the international stage in the 1990s and their sharp decline in recent years. Particular attention is paid to factors contributing to the decline in performance: the lack of a systematic approach to training the next generation of athletes, restrictions on participation at the international level, and increased competition from new leaders. The specifics of the organisation of competitive activities related to changes in the number of weight categories and training methods are taken into account. The decline in the medal count at world championships is not accidental, but reflects existing problems in the current system of training the national team. Recommendations are made for modernising training and restoring the leading positions of Russian Greco-Roman wrestlers in the international arena.